Endothelium-dependent vasodilation in response to Pseudomonas aeruginosa lipopolysaccharide: an in vitro study on canine arteries - Evora,P.R.B. (1998)
Early systemic arterial hypotension is a common clinical feature of Pseudomonas septicemia. To determine if Pseudomonas aeruginosa endotoxin induces the release of endothelium-derived nitric oxide (EDNO), an endogenous nitrovasodilator, segments of canine femoral, renal, hepatic, superior mesenteric, and left circumflex coronary arteries were suspended in organ chambers (physiological salt solution, 95% O2/5% CO2, pH 7.4, 37oC) to measure isometric force. In arterial segments contracted with 2 µM prostaglandin F2a, Pseudomonas endotoxin (lipopolysaccharide (LPS) serotype 10(Habs) from Pseudomonas aeruginosa (0.05 to 0.50 mg/ml)) induced concentration-dependent relaxation of segments with endothelium (P<0.05) but no significant change in tension of arteries without endothelium. Endothelium-dependent relaxation in response to Pseudomonas LPS occurred in the presence of 1 µM indomethacin, but could be blocked in the coronary artery with 10 µM NG-monomethyl-L-arginine (L-NMMA), a competitive inhibitor of nitric oxide synthesis from L-arginine. The inhibitory effect of L-NMMA on LPS-mediated vasorelaxation of the coronary artery could be reversed by exogenous 100 µM L-arginine but not by 100 µM D-arginine. These experiments indicate that Pseudomonas endotoxin induces synthesis of nitric oxide from L-arginine by the vascular endothelium. LPS-mediated production of EDNO by the endothelium, possibly through the action of constitutive nitric oxide synthase (NOSc), may decrease systemic vascular resistance and may be the mechanism of early hypotension characteristic of Pseudomonas septicemia.